How the Location of Roads and Protected Areas Affects Deforestation in North Thailand - Cropper, Maureen; Puri, Jyotsna; Griffiths, Charles (World Bank, Washington, DC, 2014)
Using plot-level data, the authors estimate a bi-variate probit model to explain land clearing, and the siting of protected areas in North Thailand in 1986. Their model suggests that protected areas (national parks, together with wildlife sanctuaries) did not reduce the likelihood of forest clearing, but wildlife sanctuaries may have reduced the probability of deforestation. Road building, by reducing the impedance-weighted distance to market, has promoted clearing, especially near the forest fringe. The authors stimulate the impact of further road building to show where road building is likely to have the greatest impact on forest clearing, and where it is likely to threaten protected areas.